The Newspapers issued in the Philippines under Japanese Occupation from 1942-1945 - Shinzo Hayase (2018)
The Japanese Imperial Army and Navy issued newspapers in their occupied territories for the Japanese soldiers and civilians, and for local residents from 1942-1945. But only the local and Japanese newspaper companies that it authorized were allowed to print and circulate news items that passed through its scrutiny. This paper examines the newspapers in the Philippines as Japan's propaganda tools for its "Greater East Asia" ideals.
Keywords: Newspapers -- Philippines; Propaganda -- History; Philippines -- History -- Japanese occupation, 1942-1945